Impact of preoperative persistent or permanent atrial fibrillation on inhospital mortality after coronary artery bypass graft surgery - Cunha Sales, Marcela da; Rösler, Álvaro Machado; Simões Ferreira, Gustavo; Wlly Prediger, Vinícius; Nascimento, Jonathan Fraportti do; Lucchese, Fernando Antônio (JOURNAL OF CARDIAC ARRHYTHMIAS, 2024)
Introduction: Atrial fibrillation (AF) is an arrhythmia that has a well-established impact on cardiovascular and cerebrovascular morbidity and mortality. However, the role of this arrhythmia plays on surgical risk remains uncertain. Objective: to evaluate the impact of preoperative persistent or permanent AF on in-hospital mortality after isolated coronary artery bypass graft surgery (CABG). Methods: prospective cohort with 2,377 patients submitted to isolated CABG between January 2014 and December 2021. Sixty-two variables, including baseline factors, operative characteristics, and outcomes, were analyzed. Patients were divided into two study groups: No preoperative AF (n=2,287) and preoperative persistent or permanent AF (N=90). The comparison between the groups was performed initially by descriptive and univariate analysis. Subsequently, the analysis of mortality predictors was performed using binary logistic regression - multivariate adjusted analysis. Results: patients with preoperative AF were older, had a higher prevalence of pulmonary hypertension and anemia, had lower ejection fraction and had higher surgical risk scores when compared with patients with no history of atrial fibrillation. The in-hospital death was more frequent in patients with a history of AF (3.2% vs 8.9%, P=0.010). Through the multivariate analysis, it was possible to verify that preoperative AF is independently associated with the occurrence of in-hospital mortality after CABG (OR 2.68; 95% CI 1.21-5.94, P=0.015). Conclusion: Preoperative persistent or permanent AF has been shown to have a significant impact on in-hospital mortality rates after CABG even after adjusted multivariate analysis, being an independent risk predictor for the occurrence of postoperative death.